Reflections on the structure of the European Union. - EVERLING, Ulrich (1992)
Points out that the Maastricht Treaty does not develop the Community into a Union, but instead erects a Union around the Community. Notes that the goal of integration has not been reached, only that integration has reached a stage of institutional independence and autonomy which in sum justifies it being called a Union. Discusses the form of the Treaty texts, the configuration of the Union, tasks and competencies of the Union, the constitutional and legal order of the Union, and the position of member states.